Development of a generic tool to design scroll expanders for ORC applications. (25th October 2016) - Garg, Pardeep; Karthik, G.M.; Kumar, Prashant; Kumar, Pramod
Abstract: Successful experimental studies on the scrolls that are reverse engineered to operate in the expansion mode recommend their use in the ORCs over conventional turbines when the power capacities lie in the range of 1–50 kWe. However, when it comes to the design of a new scroll expander for a particular ORC requirement, an ORC engineer hardly finds any guidelines in terms of selecting the geometric features of scroll such as height, involute base circle radius, and number of expansion chambers. This paper is motivated by such a philosophy wherein we develop a generic framework, capable of obtaining efficient scroll geometries for any ORC specifications including the working fluid. The process of finding the most efficient geometry involves the estimation of losses inherent to scroll such as leakages, supply pressure drop, under/over expansion and other mechanical losses. This framework is validated using the experimental data available in literature and a detailed case study of designing scroll expanders for R134a is presented to highlight the effect of operating conditions and geometric features on the loss mechanisms. It is found that there exists a unique scroll height (or aspect ratio) that results in the maximum isentropic efficiency for the given set of operating conditions. Further, this work is extended to the design of scroll expanders for various working fluids in the ORC regime. In this regard, it is found that high condenser pressure fluids such as R134a, R152a and isobutane are more suited in scroll expanders as their cycle volume ratio matches with the optimum scroll volume ratio (2–5).